ФАКТОРЫ, СПОСОБНЫЕ ОКАЗЫВАТЬ ВОЗДЕЙСТВИЕ НА ХАРАКТЕР ЯЗЫКОВОЙ СИТУАЦИИ - Татьяна Плешкова (Studia Rossica Posnaniensia)
Extralinguistic factors depicting the language situation specifics in Arkhangelsk Region territory were characterized in the article. Political-economic and social changes as well as migration and demographic processes belong to them.